Degradation of Spent Oil Contaminated Soil Using Fungi from Organic Manure (2019)
Soil is the key component of natural ecosystem because environmental sustainability depends largely on a sustainable soil ecosystem. Microbial breakdown of hydrocarbon pollutants is generally a very slow proceed, but it could be optimum biodegradation can only occur if the right environmental condition such as pH, temperature, nutrients and relevant microbial consortia are present, as well as the pollution of petroleum hydrocarbons caused a major change in the physical and chemical properties of the soil. The aim of this study is to determine the total petroleum Hydrocarbon degradative potentials of the intrinsic microbes. Two kilograms (2kg) of soil was thoroughly mixed with 200ml and 400ml of spent oil to give 5% and 10% contamination levels and a set of control was kept at 0%, 10%(w/w) each of the organic manure from poultry litter (PL), Cow dung (CD), and the mixed poultry litter and cow dung (MPLCD) was individually introduced into each spent oil contaminated soil and the rate of biodegradation was monitored for a period of 12 weeks. The percentage of total Petroleum Hydrocarbon (TPH) loss was significantly higher in the soil contaminated with MPLCD (40.46%) followed by PL (35.53%) and CD (27.70%) while 32.42% loss only was recorded in the soil contaminated with 10% spent oil and amended with MPLCD while PL was 30.04% and 25.60% for CD. The hydrocarbon-initializing fungi isolated and identified include Aspergillus spp. and Penicillium spp. The amendment of spent oil contaminated soil with organic manure can significantly enhance the rate of biodegradation of petroleum hydrocarbon. These activities can be used to remove or neutralize the contaminants of the soil, by petroleum hydrocarbon